The role of intelligent systems in financial auditing and financial fraud - Andrade, Victor Gomes (2022)
Intelligent systems have become increasingly prominent in the current competitive and changing corporate atmosphere. Although people in firms still handle many jobs, intelligent systems will become more prominent in the short/medium future and will execute everyday jobs presently executed by people considerably more effectively. Businesses must adapt and consider how human and intelligent systems skills might be combined. This study focuses on the financial auditing profession since these individuals devote a lot of time doing repetitive tasks that intelligent technologies can straightforwardly and swiftly execute. This study investigates the influence of Artificial Intelligence, Big Data, and the Internet of Things on this profession. As per the survey, financial auditors understand that intelligent systems are the way to go as a tool to help them perform their jobs, but they are still concerned to change. Employing these systems in daily financial auditing tasks is seen as having a lot of benefits by these professionals and intelligent systems professionals, but there are still some barriers to overcome. Regardless of the circumstances, intelligent systems will significantly influence financial audits.